2021
DOI: 10.1002/stvr.1760
|View full text |Cite
|
Sign up to set email alerts
|

Generating and selecting resilient and maintainable locators for Web automated testing

Abstract: Summary Web user interface (UI) test automation strategies have been dominated by programmable and record–playback approaches. Of these, record–playback allows creating automation tests easily and reduces the cost of test generation. However, this approach increases the cost of test maintenance due to its unstable generated locators for identifying UI objects during playback. In this paper, we propose a new approach to generating and selecting resilient and maintainable locators. Our approach consists of two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Nguyen et al recently suggested an approach that can generate resilient locators by using a new way of constructing XPaths that relies on semantic structures and neighbor web elements and a rule-based method for selecting the best (i.e., most robust) one [49].…”
Section: B Resilient Locatorsmentioning
confidence: 99%
“…Nguyen et al recently suggested an approach that can generate resilient locators by using a new way of constructing XPaths that relies on semantic structures and neighbor web elements and a rule-based method for selecting the best (i.e., most robust) one [49].…”
Section: B Resilient Locatorsmentioning
confidence: 99%